2017
DOI: 10.1097/md.0000000000008240
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumor (GIST) with liver metastases

Abstract: Approximately 40% to 50% of gastrointestinal stromal tumor (GIST) patients will have recurrence or metastases after resection of the primary lesion, and the most common affected sites will be liver and peritoneum. Imatinib has been considered as the first-line therapy of metastatic GIST. Surgery for metastases is proposed when possible. Furthermore, there are controversies concerning hepatic resection and systemic tyrosin kinase inhibitors (TKIs). The therapeutic conditions and long-term outcome of GIST patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Similar result was observed in a previous study. 12 One possible reason is that gene mutation weighs more heavily in the development and progression of GIST than in that of colorectal cancer, with secondary mutation found in as high as 80% of progressed GIST lesions. 14 Another reason is that TKI therapy for GIST is far more effective than chemotherapy for colorectal cancer, and the impact of metastatic phase is overshadowed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar result was observed in a previous study. 12 One possible reason is that gene mutation weighs more heavily in the development and progression of GIST than in that of colorectal cancer, with secondary mutation found in as high as 80% of progressed GIST lesions. 14 Another reason is that TKI therapy for GIST is far more effective than chemotherapy for colorectal cancer, and the impact of metastatic phase is overshadowed.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some studies dealing with patients with GLM, their baseline values and treatment strategies varied greatly: some patients had previous metastasis before spreading to the liver, and some did not receive TKI therapy after the operation. 11 , 12 These variations were associated with a poor survival. 13 Therefore, it is necessary to reassess the value of surgery in this subset of patients with a more balanced dataset.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that more than half of the GIST patients had metastases upon presentation at medical institutions, and the liver was the most common site [ 8 ]. Although complete surgical resection with negative margins is the standard treatment for GIST, over 50% of patients develop recurrence or metastasis [ 9 , 10 ], with liver metastasis being the main metastatic pattern of GIST [ 11 , 12 ]. Hence, the poor prognosis of GISTs might be related to the status of liver metastasis (LIM).…”
Section: Introductionmentioning
confidence: 99%
“…GISTs primary to the liver are quite rare (33) when compared to their much more common counterparts in the digestive tract (28). Since GISTs have a well-known propensity to spread to the liver, most GISTs encountered on a liver biopsy will be a metastatic deposit (34,35). Most cases of GIST will be the spindle cell type, composed histologically of a relatively uniform sheet of spindle cells.…”
Section: Differential Diagnosismentioning
confidence: 99%